Shortcuts to God - "Jampolsky, Gerald G" (New Delhi, 2000)
This book describes a path to a deeply personal spirituality. No doctrine. No dogma. No rituals required. After 25 years of living and teaching these principles, Dr Jampolsky offers a fresh look at our purpose in life, a map of short-cuts, 18 inspired lessons for personal transformation, and reflections and meditations to solidify the process.
Keywords: Philosophy-India